Safety and therapeutic potential evaluation of Cefotaxime plus Polymyxin B against polymyxin-carbapenem resistant Klebsiella pneumoniae in a murine model - Mariana Carvalho Sturaro; Nathalia da Silva Damaceno; Gleyce Hellen de Almeida de Souza; José Eduardo Souza Echeverria; Ediane Bortolotte Cornelius; Luccas Pereira Pires; Pedro Vinícius Dias Bassetto Silva; Bárbara Maria Cristaldo Gomes; Thiago Leite Fraga; Osmar Nascimento Silva; Luana Rossato; Simone Simionatto (PLoS ONE, 2026)
Objectives This study aimed to evaluate the toxicity and antibacterial efficacy of Cefotaxime/Polymyxin B combination (CTX/PMB) against a polymyxin-carbapenem-resistant (PC-R) Klebsiella pneumoniae strain, using a mice model. Methods and results A single-dose toxicity assay was conducted in BALB/c mice, divided into control and CTX/PMB-treated groups receiving low, medium, or high CTX doses. Body weight, food, and water intake were monitored for 14 days. After euthanasia, organ weights and plasma biochemical markers were analyzed. Medium- and high-dose groups maintained stable weight and intake. High-dose mice exhibited reduced right kidney and liver weights and elevated urea levels. Creatinine was at the upper limit in all groups, including one control mouse. For antimicrobial efficacy, BALB/c neutropenic mice infected with PC-R K. pneumoniae K18 were assigned to naïve, mock-treated, CTX, PMB, or CTX/PMB groups. Treatments were given every 12 h, and after 24 h, blood was collected to quantify bacterial load. CTX/PMB significantly reduced blood bacterial load and improved clinical condition compared to other groups. Conclusion CTX/PMB showed therapeutic potential in treating PC-R K. pneumoniae . However higher CTX doses may potentiate PMB-associated toxicity. These findings encourage further investigation in advanced preclinical models and clinical settings to fully elucidate CTX/PMB therapeutic potential and optimize dosing regimens.